2022
DOI: 10.1523/jneurosci.1644-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Tmem59 Deficiency Impairs Phagocytosis of Synapse and Leads to Autism-Like Behaviors in Mice

Abstract: Synaptic abnormality is an important pathologic feature of autism spectrum disorders (ASDs) and responsible for various behavioral defects in these neurodevelopmental disorders. Microglia are the major immune cells in the brain and also play an important role in synapse refinement. Although dysregulated synaptic pruning by microglia during the brain development has been associated with ASDs, the underlying mechanism has yet to be fully elucidated. Herein, we observed that expression of Transmembrane protein 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“… 21 , 22 On the other hand, microglia also play a key role in synaptic refinement, and abnormal microglia show dysfunctional synaptic pruning ability, which is an important cause of neural dysfunction. 23 In our study, Bergaptol treatment significantly improved cognitive impairment in LPS-treated mice. Further analysis of changes in hippocampal neuron morphology in mice revealed that Bergaptol treatment significantly reduced the level of nucleus fixation in hippocampal neurons of LPS-treated mice and alleviated the reduction in hippocampal neuron spine density.…”
Section: Discussionsupporting
confidence: 57%
“… 21 , 22 On the other hand, microglia also play a key role in synaptic refinement, and abnormal microglia show dysfunctional synaptic pruning ability, which is an important cause of neural dysfunction. 23 In our study, Bergaptol treatment significantly improved cognitive impairment in LPS-treated mice. Further analysis of changes in hippocampal neuron morphology in mice revealed that Bergaptol treatment significantly reduced the level of nucleus fixation in hippocampal neurons of LPS-treated mice and alleviated the reduction in hippocampal neuron spine density.…”
Section: Discussionsupporting
confidence: 57%
“…A mouse model lacking CX3CR1 showed a transient decrease in microglia and a consequent defect in synaptic pruning during the early postnatal period. In a mouse model of microglial Tmem59 deletion, deletion of microglial Tmem59 impaired synaptic phagocytosis, leading to autism-like behavior ( Meng et al, 2022 ). In autism models, a transient decrease in microglia is followed by a synaptic pruning defect, strongly associated with autistic behaviors such as social deficits.…”
Section: Microglia Contribute To Neuroinflammation In Asd By Releasin...mentioning
confidence: 99%
“…Previous studies have revealed that the disruption of E/I balance contributes to the pathogenesis of autism spectrum disorders (ASD). 16 , 17 , 18 , 19 , 20 We, therefore, investigated if an alteration of autistic‐like behaviors occurred in the β3 E182G KI mice by evaluating their performances in social interaction and locomotor activity. In a three‐chambered social interaction test with a mouse (M) versus a toy (T), we found that the KI mice displayed obvious social deficits as reflected by a significant reduction in both number (WT: 1.24 ± 0.12, n = 16; KI: 0.92 ± 0.07, n = 13; p = 0.026; Figure 5A,B ) and time (WT: 1.33 ± 0.24, n = 16; KI: 0.67 ± 0.12, n = 13; p = 0.024; Figure 5A,C ) of the social index (SI), compared to WT controls.…”
Section: Resultsmentioning
confidence: 99%
“… 7 The β3 subunit is more broadly expressed than the β2 subunit in the mammalian brain, including cerebral cortex, hippocampus and hypothalamus, 12 , 13 and serves as one of the most important subunits regulating GABA A R function at both circuit 14 and behavioral levels. 1 , 2 , 15 , 16 Therefore, we hypothesized that mice harboring glutamate‐binding deficient GABA A Rs generated by KI of β3 Glutamic acid 182 to Glycine (E182G) mutation would have significantly diminished glutamate potentiation on most native GABA A Rs, thereby exhibiting overexcitation phenotypes.…”
Section: Introductionmentioning
confidence: 99%